ANALISIS TEKNIS DAN FINANSIAL USAHA PEMBUATAN KOPI BUBUK “KOPI ARANIO” DI DESA ARANIO - Fenny Refiana (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2023)
The aims of the research on technical and financial analysis of the business of making "Kopi Aranio" powder coffee are: (1) to know the technical implementation of powder coffee processing, and (2) to know the profit in powder coffee business activities. The research was conducted for 3 months, the research location was in Aranio Village, Aranio District, Banjar Regency. Research activities implemented include preparation, field observations, data collection, data analysis, and reporting. The results showed that: (1) technically the coffee-making business in Aranio Village, Aranio District, Banjar Regency was good, but it could not be separated from natural obstacles such as floods, rains and so on which hampered coffee marketing; and (2) it is known that the total revenue is Rp. 17,100,000, - while the total cost is Rp. 12.196.986,5, it can be seen that the amount of profit is Rp. 4.903.013,5/month